FDZ data description: RWI-GEO-POP-FORECAST: Small-scale population projection V2 - Philipp Breidenbach; Patrick Thiel; Thorben Wiebe (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Existing nationwide population projections focus on highly aggregated spatial units. The most disaggregated nationwide study is provided by the German Federal Institute for Building, Urban Affairs and Spatial Research (BBSR) and forecasts population at the county level until 2040 (BBSR, 2021). The Federal Statistical Office's projections - the benchmark for German population projections - are limited to the entire country or to the federal states. Our novel data set offers a population projection with a resolution of one square kilometer up to 2060. Since many local socioeconomic characteristics show great spatial heterogeneity, as documented by RWI-GEO-GRID (RWI - Leibniz Institute for Economic Research, 2022), the need for a small-scale population forecast becomes apparent. We closely follow the assumptions on fertility, mortality and (out) migration of the German Federal Statistical Office, so that our forecast reflects those estimates at the national level, but provides detailed information about local communities, including gender and age structure. The generated data set is made available to researchers. – – Bestehende bundesweite Bevölkerungsprognosen konzentrieren sich auf hoch aggregierte räumliche Einheiten. Die am stärksten disaggregierte bundesweite Studie wird vom Bundesinstitut für Bau-, Stadt- und Raumforschung (BBSR) vorgelegt und prognostiziert die Bevölkerung auf Kreisebene bis 2040 (BBSR, 2021). Die Vorausberechnungen des Statistischen Bundesamtes - der Maßstab für deutsche Bevölkerungsprognosen - beschränken sich auf das gesamte Land oder auf die Bundesländer. Unser neuartiger Datensatz bietet eine Bevölkerungsvorausberechnung mit einer Auflösung von einem Quadratkilometer bis zum Jahr 2060. Da viele lokale sozioökonomische Merkmale eine große räumliche Heterogenität aufweisen, wie das RWI-GEO-GRID (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022) dokumentiert, wird die Notwendigkeit einer kleinräumigen Bevölkerungsprognose deutlich. Wir folgen eng den Annahmen des Statistischen Bundesamtes zu Fertilität, Mortalität und (Ab-)Wanderung an, sodass unsere Prognose diese Schätzungen auf nationaler Ebene widerspiegelt, aber detaillierte Informationen über lokale Nachbarschaften, einschließlich der Geschlechter- und Altersstruktur, liefert. Der generierte Datensatz ist für Forschende zugänglich.
Keywords: 330